IMPROVING THE TWELFTH GRADE STUDENTS’ VOCABULARY MASTERY THROUGH STORY TELLING TECHNIQUE IN SMA SANTO PETRUS MEDAN - Simbolon, Hema M; Ginting, Fiber Yun; Sembiring, Novalina (Kairos English Language Teaching Journal, 2020)
Vocabulary mastery is the basic language aspect that must be mastered before mastering English skill. The more words the students learn, the more they can understand and express their idea in that language. When they have inadequate vocabulary, they can say little things because they do not know how to say it in that language. That is why this study was conducted in order to improve the students’ vocabulary mastery. Storytelling technique can help students for remembering or mastering vocabulary. The objectives of this study are to find out whether Storytelling technique can improve the students’ English vocabulary mastery and find out the students’ responses after being taught by using Storytelling technique. The subjects of this study were the twelfth grade students of SMA Santo Petrus Medan. In conducting this study the writer used Classroom Action Research (CAR) as the method of the study. Tests were used to gather the quantitative data. In addition, field notes and observation sheet were used to gather qualitative data. Based on the finding of this study, it showed in pre-test only 4 students (16%) who passed KKM (Mastery Minimum Criterion) and in post-test 22 students (88%). The result of this study revealed that there was a significant improvement of the students’ achievements in the pre-test and in the post-test. It could be seen from the improvement of the students’ mean score 59.52 in pre-test to 80.48 in post-test. Furthermore, the students were interested in Storytelling technique. The analysis of the questionnaire showed that most of students agree to learn vocabulary by using Storytelling technique. It could be seen from the table, it showed that total of agree 47.2%. Therefore, Storytelling technique was an effective technique in helping students to improve their vocabulary mastery.